Implementasi Metode Naive Bayes-Certainty Factor Untuk Diagnosis Penyakit Pada Kelamin Laki-Laki - Bayu Febrian Putera Ammal; Nurul Hidayat; Suprapto Suprapto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Sex has become the most basic instinct of every creature in this mother Earth. Sex is essential to survive a life as in preserving the species' generation. However, the lack of sex education leads into a free sex lifestyle. This jeopardize lifestyle has increased these years with its sexually transmitted disease as one of the following risks. Sexually Transmitted Disease (STD) which are infecting men and can be contagious to other people includes Gonorrhea, Syphilis, Herpes, HIV/AIDS, and Human Papilloma Virus (HPV). Thus, symptoms can be an indicator to discover what disease which infect the human's body. However, some sexually transmitted diseases have similar symptoms that might lead in a wrong first aid for the patients themselves and ironically result in the severity of that disease. Besides, a wrong first aid will cause the disease to be more contagious especially to that patient's intimate partner as well. Therefore, Naive Bayes-Certainty Factor is needed to reduce the misdiagnosed. This study used Naive Bayes-Certainty Factor method in diagnosing the STD in men. The analysis was done by comparing the results of the system diagnosis with the expert diagnosis. From 35 data testing, the result showed that there was 85% of the accuracy in diagnosing Men Sexually Transmitted Disease by using expert diagnosing system with Naive Bayes-Certainty Factor method.